Transmission of Environmental Knowledge and Land Skills among Inuit Men in Ulukhaktok, Northwest Territories, Canada - Pearce, T; Wright, Harold; Notaina, R; Kudlak, A; Smit, B; Ford, J; Furgal, C (Human Ecology, 2011)
The transmission of environmental knowledge and land skills was studied among Inuit men in Ulukhaktok, Northwest Territories, Canada. A list of 83 skills important for safe and successful harvesting was generated with 14 active hunters and elders, and examined with a sample of 47 men. This research found that land skills continue to be transmitted most often from older to younger generations through observation and apprenticeship in the environment. However there is a difference in the rate of skills transmission among generations, with average transmission rates lowest among younger respondents. Some skills were transmitted well among younger respondents including general hunting and camp-related skills, but others such as traveling on the sea ice and traditional navigation skills were not. Loss of certain skills and incomplete transmission of others were related to the absence of skills teachers, loss of native language, and changes in the educational environment.